2007
DOI: 10.1093/annhyg/mem008
|View full text |Cite
|
Sign up to set email alerts
|

Modelling Exposure in Flour Processing Sectors in The Netherlands: a Baseline Measurement in the Context of an Intervention Program

Abstract: The dataset serves as a baseline estimate and will be compared with a post intervention survey in the near future. The information obtained on control measures can be used to optimize the intervention scenarios that will be implemented in the different sectors by external occupational hygienists. The predictive exposure models will provide a relevant measure of average personal exposure that will be used in the sector wide health surveillance system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Cleaning the bins in bakeries and maintenance cleaning in mills have given peak values (total flour dust) of 390 and 458 mg/m 3 , respectively. [ 34 ] Meijster et al [ 72 ] studying exposure to total dust in industrial and traditional bakeries, factories producing ingredients for the baking industry (i.e., pre-mixes based on flour or other bulk and specialized additive mixtures for bread or pastry) and flour mills recorded the maximal concentrations on the extremely high levels reaching 292, 318, 627 and even 1837 mg/m 3 , respectively.…”
Section: Occupational Exposures To Flour Dustmentioning
confidence: 99%
“…Cleaning the bins in bakeries and maintenance cleaning in mills have given peak values (total flour dust) of 390 and 458 mg/m 3 , respectively. [ 34 ] Meijster et al [ 72 ] studying exposure to total dust in industrial and traditional bakeries, factories producing ingredients for the baking industry (i.e., pre-mixes based on flour or other bulk and specialized additive mixtures for bread or pastry) and flour mills recorded the maximal concentrations on the extremely high levels reaching 292, 318, 627 and even 1837 mg/m 3 , respectively.…”
Section: Occupational Exposures To Flour Dustmentioning
confidence: 99%
“…Flour dust is a heterogeneous substance with respiratory sensitizing properties and long-term exposure to it may cause acute or chronic respiratory disease [ 8 ]. Several studies showed that prevalence of sensitization for wheat allergens and fungal a-amylase and OAD is high among workers exposed to flour dust [ 9 ]. This can have a tendency to cause respiratory ailments [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In both groups (bakery and auto body shop workers), exposure was estimated based on existing data sets of personal airborne exposure measurements (Pronk et al 2006a; Meijster et al 2007). Cumulative monthly hexamethylene diisocyanate (HDI) exposure was estimated using task-based measurements of airborne diisocyanates combined with self-reported monthly frequencies of task completion as was described previously (Pronk et al 2007).…”
Section: Methodsmentioning
confidence: 99%
“…This exposure metric was then divided by the self-reported average number of hours worked per month to determine the long-term average isocyanate exposure of these workers (μg-NCO*m −3 ) that facilitated comparison with the bakery workers. Average wheat exposure for bakery workers was estimated using subjects’ work characteristics (exposure determinants) reported on the questionnaire combined with an exposure model constructed by Meijster et al (2007), to predict average wheat exposures (μg-dust*m −3 ) for each subject.…”
Section: Methodsmentioning
confidence: 99%